IDENTITAS JAKARTA MELALUI KARYA KREATIF LALEILMANINO BERJUDUL DJAKARTA - Malya Faiza Ayudira; Ela Yulaeliah; Warsana (Sorai: Jurnal Pengkajian dan Penciptaan Musik, 2024)
The creativity in the musical work titled "Djakarta", created by the alliance of producers and songwriters: Laleilmanino, was inspired as a gift for Jakarta’s 497th anniversary in 2024. This research aims to understand how musical creativity can represent the cultural identity of a metropolitan city through the fusion of traditional Betawi music (tehyan and kendang) with easily accessible pop music elements. A qualitative method is used to observe the phenomenon of creativity in Laleilmanino’s song "Djakarta." In its creation process, the song demonstrates that "Djakarta" successfully produces a musical product with a pop identity that is catchy yet retains its traditional roots. This fusion led "Djakarta" to be nominated for the 2024 AMI Awards as Best Pop Music Arrangement.